Trade Restrictions in the Context of Foreign Trade Liberalisation - Kateryna Puhachevska (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The relevance of the article is determined by the study of scientific works on the impact of the foreign trade component on economic growth, since as of now the idea of the positive impact of foreign trade and its liberalisation on economic growth prevails. At the same time, discussions on trends in the liberalisation of foreign trade are part of the problem, which is the contradictory impact on the economic development of the free crossborder movement of goods, capital, and labor. The aim of the article is to study trade restrictions in the context of foreign trade liberalisation. Achieving this goal is based on methods of analysis and synthesis, induction and deduction, that are grounded on an integrated approach. It is noted that at a high level of economic development, economic liberalisation allows increasing the benefits of foreign trade, but the issues related to the opening of domestic markets in the countries of economic periphery remain controversial. The article considers the essence and classification of foreign trade restrictions. The views of scholars of the leading economic schools on the relationship between trade liberalisation and economic growth are characterised. It is determined that the main trends in the liberalisation of foreign trade are: expanding the scope of regulatory measures by both national governments and global trade institutions; coordination and intensification of international cooperation in the areas of multilateral liberalisation of foreign trade; the growth of non-tariff restrictions on the way of the international trade development. The results of the study allow deepening the understanding of the peculiarities of ensuring national economic interests in the conditions of dynamisation of foreign trade